Status, Gaps and Challenges in Menstrual Health in India: A Systematic Review - Priyanka Joshi; Rakesh Sharma; Geeta Jain; Gunjot Kaur; Prasuna Jelly (Preventive Medicine: Research & Reviews, 2025)
This systematic review was conducted to evaluate the current status of menstrual hygiene management among adolescent girls in India. Inclusion criteria were (1) studies from India, (2) articles published in peer-reviewed journals, (3) any study design reporting menstruation health, (4) articles published in the English language and (5) study participants being adolescent girls aged 12–19 years. All the studies were systematically reviewed, and their quality was assessed using the Newcastle–Ottawa Scale. A total of 52 studies were included. The studies reported that majority of adolescent girls had a basic understanding of menstruation mechanics and predominantly used sanitary napkins. However, challenges persisted due to cultural taboos and inadequate hygiene facilities, particularly in rural schools and communities. Despite these hurdles, there was a rise in the awareness and the use of sanitary products over the years; furthermore, there was a positive impact of various government programmes and schemes, which has enhanced the knowledge and improved menstrual health management among adolescent girls, resulting in reduced absenteeism from schools. Further, a very few studies reported about the discard of menstrual waste material, and majority were not aware of the discard method. There is a gap in the effectiveness of governmental programmes, which aim to enhance menstrual hygiene by providing the sanitary products and the waste disposal facilities. To improve menstrual hygiene in India, comprehensive educational initiatives are needed to address misconceptions and stigma, when simultaneously enhancing access to affordable sanitary products and environmentally safe disposal facilities.